Structural and dielectric properties of Bi2O3 nanoparticles synthesized at different temperatures. (2023) - Karma, Nikita; Siddiqui, Kamran; Harinkhere, Disha; Yadav, Anand; Kaurav, Netram
Abstract: In the present work, Bi2 O3 nanoparticles were synthesized by auto combustion method (auto chemical method). X-ray diffraction pattern confirmed that α- Bi2 O3 nanoparticles were synthesized and possessed Monoclinic Crystal structure (P21/c space group). Dielectric properties possess significant value with low loss factor. Ac conductivity is increases due to the de-trapping of charge carriers different trapping centers. Real part of Modulus (Mʹ) rises and reaches a maximum constant value at higher frequencies for both samples. This type of behavior would support conduction phenomena. There is an asymmetric broadening of the peak in imaginary part of modulus (Mʹʹ) at 700 ˚C, which indicates that it is non-Debye type relaxation.